KARAKTERISTIK FISIKO-KIMIA DAN FUNGSIONAL PATI SAGU IHUR TERMODIFIKASI DENGAN HEAT MOISTURE TREATMENT - Priscillia Picauly; Esau Damamain; Febby J. Polnaya (Jurnal Teknologi dan Industri Pangan, 2017)
The objective of this study was to characterize the properties of Heat Moisture treatment (HMT) modified ihur sago starch with different moisture contents. The starch was modified with HMT at 110°C after being adjusted to various moisture contents (23, 28, or 33%) for 4 h. The physico-chemical and functional properties of the native and modified HMT Ihur sago starch observed were color, swelling power, solubility, paste clarity, moisture content, ash content, amylose content, phenol content, and resistant starch (RS) content. Results of this study showed that the HMT starch has a higher degree of lightness (L*), redness (a*), and yellowness (b*), solubility (4.85-5.38%) but lower swelling power (44.06-47.47 g/g) than the native starch which has a solubility and swelling power of 4.90% and 50.72 g/g, respectively. Paste clarity was found to decrease along the storage period. In addition, higher moisture content (11.81-13.20%), but lower amylose (14.81-23.52%), phenol (2.50-4.04%), and RS (5.4-6.1%) content were observed than the native starch with amylose, phenol, and RS content of 27.18, 7.91, and 6.5%, respectively.